Preensão para escrita manual em universitários: diferentes tipos e sua relação com teste de destreza fina - Sime, Mariana Midori (Universidade Federal de São Carlos, 2012)
Handwriting is indispensable in daily work, in academia and in the assertion of personal identity, although it may seem less used today. In clinical practice of occupational therapy, children, adolescents and adults are often referred by presenting postural imbalances and compensatory motor alterations in various activities, including handwriting. During the execution of this task, there is the influence of motor predominant proximal or distal upper limb, depending on the type of grasp that is used in maintaining the pencil in his hand and the performance of fine manual dexterity. These aspects define the classification grasps in patterns: primitive grasp patterns, transitional grasps patterns and mature grasp patterns. This study was divided into two phases. In Phase I we identified through filming, the different types of grasps for handwriting and the prevalence of each type in 806 university students, aged over 18 years, right-handed, of both genders and without functional impairment in upper limbs. For Phase II, 40 subjects were randomly selected among those classified in the previous phase as grasps patterns mature and transition, 20 in each group. We applied the Purdue Pegboard Test, and analyzed the relationship between the manual dexterity and fine these grasp patterns. Data were statistically analyzed using descriptive prevalence (Phase I) and the Student's t-test for independent samples with a significance level of 0.05 (Phase II). The phase I results indicate a higher prevalence of mature grasps at the surveyed population, especially the dynamic tripod, supporting the literature. There was no significant difference between the performance of manual dexterity and the two patterns grasps used by adults for handwriting, suggesting that the functionality is independent of the grasp pattern. However, although there is no difference in functionality, it is known that the extensive use of the proximal muscles of the upper extremities can lead to pain, discomfort and diseases that, in the long term, can compromise the performance and quality of life of people who do. It is important to be aware of the importance of the involvement of occupational therapists in the school environment to stimulate and guide the most appropriate use of upper limb. Adult intervention is necessary in order to prevent or handle changes in functional performance between those seeking assistance with complaints of pain and discomfort in the upper limb.
Keywords: Terapia ocupacional; Capacidade motora; Desempenho psicomotor; Avaliação; Escrita Manua; Destreza Motora; Estudantes; Occupational therapy; Handwriting; Motor skills; Students; Psychomotor performance; Evaluation; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL